A trindade como dramatis personae no Theo-Drama de Hans Urs von Balthasar - Oliveira, Isaque Sicsú de (2018)
The present dissertation contemplates an investigation on the trinitarian dogma, as exposed and outlined by the Swiss theologian Hans Urs von Balthasar (1905-1988). The emphasis lies on the dramatic Balthasarian method. That is, the investigation seeks to clarify how Balthasar presents his vision of the Trinity in the second episode of his trilogy, Theo- Drama. In addition, it seeks to show how this method can be useful in presenting the Christian faith to an increasingly skeptical audience. Balthasar is one of the leading theologians of the 20th century. Its theological production is extremely long. Throughout his life, there were hundreds of works produced. The present dissertation concentrates mainly on the exposition of the trinitarian dogma in the five volumes of theodramik: (1) Prolegomena; (2) Dramatis Personae: Man in God; (3) Dramatis Personae: Persons in Christ; (4) The Action; (5) The Last Act. The hypothesis of the present dissertation is based on the way in which Balthasar presents the three Persons of the Trinity, as personages within a redemptive drama, in which the Father appears as the playwright and architect of the history of the redemption; the Son appears as the main character in the redemptive history, performing his role to the last consequences; and the Holy Spirit as the great drama director and guiding agent who guides the main character; For this, the first part of the dissertation concentrates on a brief summary of the life and work and distinctive features of the thought of Balthasar, trying to show how his geographical and historical locus was determinant in the construction of his theological convictions. Next, the doctrine of the Trinity is investigated in its classic dogmatic formulation, passing through Scripture, history of theology, main characters in the process of theological refinement of the Trinity, eventual doctrinal dissonances, culminating in an exposition of the balthasarian argumentation of the Trinity. Finally, it focuses on the way Balthasar was influenced by the theology of Karl Barth and how this robust theological dialogue can be a prototype of a respectful dialogue between Catholic and Protestant traditions within their convergences and divergences